Chapter Writing, textuality, politics in the Lucca of Bishops Berengar and Ambrose (837-852) - Tomei, Paolo (Reti Medievali E-Book, 2022)
The article consists of two intertwined sections. In the first, I intend to reconstruct the processes of political and social transformation that took place in Lucca under the actions of Bishops Berengar (837-843) and Ambrose (843-852): foreigners appointed in succession by the Court. In order to do this, I will take the viewpoint offered by the numerous private charters preserved in the Archivio Storico Diocesano of Lucca. Secondly, I will present the first results of a study on the manuscripts of the same period preserved there - an heritage not yet fully explored and appreciated. I will focus in particular on the most-recently entered text in ms 490: the so-called Dicta Gelasii papae. It was written in a Carolingian hand that Armando Petrucci has compared to that of Bishop Berengar. The text constitutes an exceptional insight into the turmoil that animated the sacred palace after the «penitential reform» of 813, and which spread throughout the Empire within a general movement of correctio.